Pimpinella ibradiensis (Apiaceae), an unusual new species from Turkey - Çinbilgel, İlker; Eren, Özkan; Duman, Hayri; Gökceoğlu, Mustafa (Phytotaxa, 2015)
Pimpinella ibradiensis, an unusual new species found in the Toka Yayla (İbradı, Antalya) in southern Anatolia, is described and illustrated. Site conditions, synecology and conservation status of P. ibradiensis are considered. In light of the comparison with the other closely related four species, namely P. nephrophylla, P. flabellifolia, P. sintenisii and P. paucidentata, its similarity within the genus are discussed. P. ibradiensis is easly distinguished from its relatives by its white petals, presence of bracts and bracteoles, larger fruits (4–5.5 × 1–2 mm), and having serrulate basal leaves with 60–95 strongly cartilaginous teeth along margins. The geographical distribution of P. ibradiensis and closely related species are mapped and the identification key of those species is updated.